2006
DOI: 10.1177/0145721706291760
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Self-efficacy, and Outcome Expectations

Abstract: Psychosocial variables investigated in this study were not related to health outcomes of type 2 diabetes. Caucasians and African Americans were similar in these variables. It is important to investigate the relationships between other variables (eg, age, duration of diabetes, education) and self-care behaviors and glycemic control. Although African Americans experience higher rates of diabetes-related complications than Caucasians do, this may possibly be due to other factors (eg, heredity, financial barriers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 33 publications
2
63
1
1
Order By: Relevance
“…Since the higher expectations of individuals about the outcomes of an action could increase the probability of demonstrating the cited behaviors [28] and given that the mean scores of adherence to a healthy diet in the patients had significantly augmented following the educational intervention, it seemed that this intervention had been able to effectively improve their nutritional behaviors through enhancing the expected outcomes. Although the results of the study by Chlebowy et al [29] did not shed light on a relationship between expected outcomes and self-care behaviors in patients with T2D, the findings of the investigation by Williams and Bond revealed that the expected outcomes had moderated the relationship between self-efficacy and self-care behaviors in a way that the combination of self-efficacy and strong beliefs in the outcomes could prove to be more effective. The results of the present study also demonstrated a significantly positive relationship between patients’ self-efficacy and expected outcomes [30].…”
Section: Discussionmentioning
confidence: 94%
“…Since the higher expectations of individuals about the outcomes of an action could increase the probability of demonstrating the cited behaviors [28] and given that the mean scores of adherence to a healthy diet in the patients had significantly augmented following the educational intervention, it seemed that this intervention had been able to effectively improve their nutritional behaviors through enhancing the expected outcomes. Although the results of the study by Chlebowy et al [29] did not shed light on a relationship between expected outcomes and self-care behaviors in patients with T2D, the findings of the investigation by Williams and Bond revealed that the expected outcomes had moderated the relationship between self-efficacy and self-care behaviors in a way that the combination of self-efficacy and strong beliefs in the outcomes could prove to be more effective. The results of the present study also demonstrated a significantly positive relationship between patients’ self-efficacy and expected outcomes [30].…”
Section: Discussionmentioning
confidence: 94%
“…20,21 Given that the study participants were less educated and reported lower incomes compared with people from a larger metropolitan city, it was possible that they might have had low health literacy and limited access to systematic education on self-management of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…19 For PMT, it was hypothesized that response and barrier self-efficacy would predict intention, which in turn would predict 3-month MVPA. 17,18 It was also hypothesized that barrier self-efficacy 16,20 and outcome expectations 21,22 would predict 3-month MVPA within SCT. Finally, it was hypothesized that past MVPA, social support from family and friends, mood (ie, depression and anxiety), modeling, and the environment (ie, availability of home PA equipment) would all predict barrier self-efficacy.…”
Section: B R I E F R E P O R Tmentioning
confidence: 99%